Produktivitas Pengusaha Mikro: Variabel Anteseden dan Pengaruhnya Terhadap Keberlanjutan Kinerja Komunitas Jember Ekonomi Kreatif (JEKa) di Jember - Hary Sulaksono; Tamriatin Hidayah (STIE Mandala Jember, 2021)
The existence of micro businesses plays an important role as a driver of the country's economy. including successfully contributing to the Gross Regional Domestic Product (GRDP) for the district of Jember. At present in the 4.0 era, being promoted is a micro business in the JEKa community that collaborates with the Jember Cooperative Office and UMKM. Aim to the study are: To find out and test the effect of business consulting variables, results marketing facilities, job skills training, issuance of SKUs on the productivity of microbusinesses in the JEKA community in Jember district; To find out and test the effect of micro business productivity variables on the sustainability of performance in the JEKA community in Jember district; To find out and test the effect of business consulting variables, results marketing facilities, job skills training, issuance of SKUs on performance sustainability in the JEKA community in Jember district. Analysis method is Path analysis. The results of this study are Business consultation variables has a significant positive effect on productivity of microbusinesses in Jember Regency, except work skill training; micro business productivity has a significant positive effect on the sustainability of performance in the JEKa community in Jember district; the effect of micro business productivity variables on the sustainability of performance in the JEKa community in Jember district has a significant positive effect on productivity of microbusinesses in Jember Regency, except work skill training.Keywords: Business consultation, Productivity, sustainability of performance, JEKa community